ANALISIS POTENSI KEBANGKRUTAN SEBAGAI DAMPAK PANDEMI COVID-19 PADA PERUSAHAAN SUB SEKTOR RESTORAN, HOTEL DAN PARIWISATA DI BURSA EFEK INDONESIA - Paul Usmany; Linda Grace Loupatty` (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This study aims to analyze the potential for bankruptcy of restaurants, hotels and tourismsub-sector companies listed on the Indonesia Stock Exchange during the Covid-19pandemic, using the ratio of net working capital to total assets, retained earnings to totalassets, EBIT to total assets, and book value of equity to book value of total debt in theAltman Z-Score Model. The population in this study were all companies in the restaurant,hotel and tourism sub-sector listed on the Indonesia Stock Exchange in 2020. The sampleused was 35 companies obtained using a saturated sampling technique (CensusTechnique). This research data uses secondary data, namely the annual reports ofcompanies in the restaurant, hotel and tourism sub-sectors listed on the Indonesia StockExchange in 2020. The data analysis method uses the Altman Z-Score MultivariateAnalysis (MDA) model III. The results showed that the potential for bankruptcy occurredin 58% of companies in the Restaurant, Hotel and Tourism Sub-sector on the IndonesiaStock Exchange. As many as 11% are in the gray area category, and 31% of companiesdo not experience financial problems so they are unlikely to go bankrupt. There are 8 companies that have a negative ratio of Net Working Capital to Total Assets, 6 companiesthat have a negative ratio of Retained Earning to Total Assets (RE/TA), 17 companieshave a ratio of Earning Before Interest and Tax to total assets (EBIT/TA). negative ones.And all companies have a positive ratio of Book Value of Equity to Book Value of TotalDebt. There are 9 companies experiencing significant financial distress so they must bedelisted in 2020 from the Indonesia Stock Exchange.